Monitoring of occupational and environmental aeroallergens – EAACI Position Paper. Issue 10 (4th August 2014) - Raulf, M.; Buters, J.; Chapman, M.; Cecchi, L.; de Blay, F.; Doekes, G.; Eduard, W.; Heederik, D.; Jeebhay, M. F.; Kespohl, S.; Krop, E.; Moscato, G.; et al.
Abstract Exposure to high molecular weight sensitizers of biological origin is an important risk factor for the development of asthma and rhinitis. Most of the causal allergens have been defined based on their reactivity with IgE antibodies, and in many cases, the molecular structure and function of the allergens have been established. Significant information on allergen levels that cause sensitization and allergic symptoms for several major environmental and occupational allergens has been reported. Monitoring of high molecular weight allergens and allergen carrier particles is an important part of the management of allergic respiratory diseases and requires standardized allergen assessment methods for occupational and environmental (indoor and outdoor) allergen exposure. The aim of this EAACI task force was to review the essential points for monitoring environmental and occupational allergen exposure including sampling strategies and methods, processing of dust samples, allergen analysis, and quantification. The paper includes a summary of different methods for sampling and allergen quantification, as well as their pros and cons for various exposure settings. Recommendations are being made for different exposure scenarios.